Ecohydrology of Surface and Groundwater Dependent Ecosystems: Concepts, Methods and Recent Developments - Thoms, Martin (2009)
Proceedings of Symposium JS.1 at the Join Convention of the International Association of Hydrological Sciences (IAHS) and the International Association of Hydrogeologists (IAH) held in Hyderabad, India, 6-12 September 2009. IAHS Publication 328 ISSN 0144-7815 Book published in the UK. Go to: http://iahs.info/ And follow the instructions: Publications / Red Books / 328 You can see the titles of the papers published in the book and you can even buy it there. Contact of one of the authors: António Chambel: achambel@uevora.pt